Disclosure - Levinson, Barry; Goodall, Caroline; Demi Moore; Donald Sutherland; Dylan Baker; Roma Maffia; Rosemary Forsyth; Michael Douglas (USA Baltimore Pictures, 1995)
With his company about to merge, a happily married and successful computer expert is expecting a promotion. Instead the job goes to a woman from another plant with whom he had an affair in his bachelor days. His new boss, not only dangerously sexy but equally dangerously ambitious, tries to pick up where they left off but he just about manages to resist. As his position at work comes under increasing pressure he decides to file charges of sexual harassment. This is the last thing the company needs.
A computer specialist is sued for sexual harassment by a former lover turned boss who initiated the act forcefully, which threatens both his career and his personal life.
Michael Crichton
Language(s): English
Subtitle(s): English, Turkish, Arabic, Serbo-Croatian
Keywords: Thriller; Drama